(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to develop e-module products that can be used in learning. This research uses the Research and Development (R&D) development method with the ADDIE development model which consists of 5 main stages, namely Analysis, Design, Development, Implementation, and Evaluation. The validity test was carried out by 3 validators, namely 1 material expert validator and 2 media expert validators. The data collection instrument used material validation assessment questionnaires, media validation, student response questionnaires, and pre-test post-test questions to test effectiveness. Based on the results of the feasibility test, the results were obtained from material validators with a percentage of 94.14% with a very valid category. The results of the joint validation of media expert I and media expert II validators were obtained with a percentage of 98.33% with a very valid category. The results of the feasibility test of the e-module developed were declared very practical, with a percentage of 93.58%. The results of the effectiveness test showed that the tcal>table so there was a significant difference between the pre-test and the post-test. The results of the effectiveness test show that this e-module product is effective and can be used. Based on the results of its validity, practicality, and effectiveness, it can be concluded that the Student Centered Learning (SCL) e-module developed is valid, practical, and effective to be used in learning Pancasila Education in grade VII of junior high school.